Bacteriophage Mediated Killing of Staphylococcus aureus In Vitro on Orthopaedic K Wires in Presence of Linezolid Prevents Implant Colonization - Kaur, Sandeep (Public Library of Science, 2014)
BACKGROUND: Infections of bone and joint tissues following arthroplasty surgeries remain a major challenge in orthopaedic settings. Methicillin resistant Staphylococcus aureus (MRSA) is recognised as an established pathogen in such infections. Combination therapy using linezolid and bacteriophage impregnated in biopolymer was investigated in the present study as an alternative strategy to prevent MRSA colonisation on the orthopaedic implant surface. METHODOLOGY: Coating of stainless steel orthopaedic grade K-wires was achieved using hydroxypropylmethlycellulose (HPMC) mixed with phage alone, linezolid alone and phage and linezolid together. The potential of these agents to inhibit adhesion of S.aureus (MRSA) 43300 on K-wires was assessed. Coated and naked wires were analysed by scanning electron microscopy (SEM) and fluorescent staining. RESULT: Significant reduction in bacterial adhesion was achieved on phage/linezolid wires in comparison to naked as well as HPMC coated wires. However, maximum reduction in bacterial adherence (∼4 log cycles) was observed on the wires coated with phage-linezolid combination. The frequency of emergence of resistant mutants was also negligible in presence of both the agents. CONCLUSION: This study provides evidence to confirm that local delivery system employing linezolid (a potent protein synthesis inhibitor) along with a broad spectrum lytic bacteriophage (capable of self-multiplication) is able to attack the adhered as well as surrounding bacteria present near the implant site. Unlike other antibiotic based therapies, this combination has the potential to significantly restrict the emergence of resistant mutants, thus paving the way for effective treatment of MRSA associated infection of medical implants.